Cross-cultural adaptation and content validation of the Nurses’ Professionalism Inventory to the Portuguese context: a methodological study - Marlene Patrícia Ribeiro; Marlene Patrícia Ribeiro; Renata Cristina Gasparino; Olga Maria Pimenta Lopes Ribeiro; Olga Maria Pimenta Lopes Ribeiro (Frontiers in Public Health, 2025)
IntroductionNurses’ professionalism is linked to the profession’s principles and plays a crucial role in the quality and safety of care in the current context of complexity in healthcare systems. In the Portuguese context, no instrument allows evaluation of the nurses’ professionalism, which led to the objective of cross-culturally adapting and validating the content of the Nurses’ Professionalism Inventory for the Portuguese context.MethodsA methodological study was carried out and comprised six stages: translation, synthesis, back-translation, committee of experts, pre-test, and approval of the process by the original author developer of the instrument.ResultsThe first three stages were completed without difficulty. Nine experts were part of the committee to validate the instrument content. They evaluated items’ semantic, idiomatic, cultural, and conceptual equivalences, clarity, and relevance. Modified Kappa and Content Validity Index were calculated for all assessments. Seven items were submitted in two rounds to achieve consensus in the assessments. The usability of the instrument was tested in the fifth stage. Forty nurses performed the pre-test and agreed that the instructions, items, and response options of the Portuguese version of the Nurses’ Professionalism Inventory were easy to understand at 95.00, 97.50, and 92.50%, respectively. The author who developed the original instrument analyzed and approved the entire process carried out.DiscussionThe cross-cultural adaptation of the Nurses’ Professionalism Inventory to the Portuguese context was carried out according to international recommendations, and the conclusion of this study will provide an instrument to assess the nurses’ professionalism in Portugal.